(untitled) (Swiss Medical Weekly, 2012)
A 13-year-old boy presented with the overall phenotypic and genotypic characterisation of Schwarz-Jampel syndrome (SJS). Windswept deformity was a major orthopaedic abnormality. Prompt diagnostic measures were applied to this patient associated with several orthopaedic procedures to move closer to acceptable appearance and function.